Application of e-Procurement in Fraud Prevention and it’s Implications in Circular Economy - Canny Canny; Didi Sundiman (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2022)
This study aim to know and determine the application of e-procurement to fraud prevention for it’s implication of a circular economy. This research is using qualitative research. The data collected by using Web scraping, by mining the data from news articles on the internet and the research about of 2,237 news articles. This study is using Natural Language Processing (NLP) between humans and computers, Bigram as a text and language processing to identify topics in news articles by using topic modelling with LDA or Latent Dirichlet Allocation method to determine the trend topic. The result from the research shows that implementation of e-procurement is considered as a way to improve the wheels of economy.